Is the service industry really low-carbon? Energy, jobs and realistic country GHG emissions reductions. (15th June 2021) - Roberts, Simon H.; Foran, Barney D.; Axon, Colin J.; Stamp, Alice V.
Graphical abstract: Highlights: The service industry not 'emissions light' when including all inputs to production. Services comprise around one fifth of emissions across five developed economies. Four key goods underpinning the UK service industry are growing. Coherent emissions policy requires services be treated as a single unified entity. Early policy implementation gives lower cumulative CO2 emissions to 2050. Abstract: In accounting for carbon emissions, the conventional wisdom is that the service industry is 'emissions light', but this is not supported when goods and other inputs to services production are included. We examine greenhouse gas emissions in detail for Australia, Germany, Italy, the UK and USA and find similarities for the service industry. Taking the UK as a case study, we apply the 7see system dynamics modelling approach that accounts for both physical capacity limits and empirical data from economic activity. Service emissions are more than doubled when imported inputs are included in a consumption basis, and that UK emissions would reduce only to 42 million tonnes annually by 2050. Tackling service emissions requires additional efficiency measures for energy-use and goods-use and considering the emission intensities of exporting countries for imports. The four key goods underpinning the UK service industry that are continuing to grow are electronic, pharmaceutical, materials and machinery. Energy policy can only deliver net-zero emissions by treating the service industry as a single unified entity, especially important because it provides the majority of employment.